1990-YILLARDA BUXORODA TURIZMNING RIVOJLANISHI VA MUAMMOLARI (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
The article examines the state of tourism in Bukhara in the first years of independence, the problems and shortcomings in the field and their causes. The factors of change in the second half of the 1990s and the processes associated with the establishment of folk arts and crafts, which contributed to the development of tourism, are analyzed on the basis of facts